F in exams : the very best totally wrong test answers - Benson, Richard, 1962- (San Francisco : Chronicle Books, 2011)
A collection of some of the more creative and hilarious ways that students have tackled challenging exam questions.
Introduction -- Chemistry -- Biology -- Physics -- Math -- Business and technology -- Psychology -- History and geography -- English.
"First published in the United Kingdom in 2008 by Summersdale"--T.p. verso.
Keywords: Examinations -- Humor